L’Antica Pizzeria da Michele as a Case Study of Traditional Speciality Guaranteed and International Franchising - Gatto, Andrea (Applied Studies in Agribusiness and Commerce, 2019)
This work explores the case study of L’Antica Pizzeria da Michele as a best practice of traditional speciality guaranteed and international franchising. Besides being one of the most ancient and successful pizzerias in Naples, da Michele is renowned all over the world for the quality of its raw products, dough processing, and output. In the last years, da Michele also started pioneering the pizza production and commerce industry with an innovative franchising model and a new company appointed to managing this latter business. This work makes use of in-depth interviews and data collected on the field. For such scope, top managers and employees of both the local and the international companies were interviewed. The study finds that da Michele managed to become a benchmark for territorial food products and, more recently, for high-standard franchising, jumpstarting a successful brand-new company and food business project.JEL Classification: O13, Q13, Q16, Q1